Leaf meals of aromatic plants as fitotherapeutics for broilers - Lara, Pedro Enrique Lara y; Ortiz, Mateo Fabian Itzá; Urquiso, Edgar Aguilar; García, José Roberto Sanginés (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to determine the growth performance and carcass yield in broilers using leaf meals as an additive phytotherapy of herbs at 0.07% in the diet. Two hundred eighty male chicks of Ross 308 strain, with 1 to 42 days of age, were randomly assigned in a completely randomized design with four treatments and seven replicates of 10 chickens each. The blends were in the proportion of 50:50 of Origanum vulgare and Piper auritum (OHL), O. vulgare and Ocimum basilicum (OA), O. basilicum and P. auritum (AHL), and one control group with flavomicim at 4%. The control group showed the highest body weight (2,385 g), feed consumption (204 g per broiler per day) and accumulative mortality (21.87%), at the end of the assay. There was no difference with OA (2,198 g) and AHL (2,023 g) blends in body weight and feed consumption. The blend OA had the lowest (1.96) and OHL had the highest (2.44) feed conversion. There was no difference in the carcass yield. The blend at 50% of O. vulgare and O. basilicum, included at 0.07% in the diet for broilers, is an alternative for promoting growth and does not alter the yield carcass.